Ensino de citologia: análise da influência de um modelo didático no ensino e na aprendizagem - França, João Pedro Rodrigues (2019)
The teaching of Cytology has its recognized importance, because it represents a relevant step for the promotion of scientific interest, going beyond the memorization of concepts. However, the students' difficulties in understanding these concepts are perceptible. The question that the present research sought to investigate was: Where did the use of didactic model contribute to the teaching and learning in Cytology for the students of the 1st grade of High School? The proposal of work tried to complement the traditional way as the classes of Cytology are often worked, aiming at the best learning of the students. The objective was to analyze how the learning about Cytology was influenced by the use of didactic model of animal cell for students of the 1st grade of High School. The research was qualitative in a public school in the state of Alagoas. The dissertation project was submitted to the Ethics Committee and approved. Data collection took place through a test of prior knowledge and post intervention applied in three classes, in order to recognize what students carried as elementary school baggage and the knowledge built after the intervention. The data obtained were analyzed by frequency of responses, by categorization and statistical analysis. The results revealed that the students present superficial knowledge about the cell, and there is still a great deal to be understood as a basis for learning in Biology. The Educational Product, titled "REPRESENTATIONAL MODEL CONCRETE OF THE ANIMAL CELL", is also presented, with the objective of supporting the teaching of Cytology and contributing to student learning. Since the knowledge about the cell by the students studied was superficial, the proposal of different teaching strategies becomes indispensable, since the act of teaching about the cell content is still attached to the memorization of the textbook.